Serpulids and other calcareous tube-dwelling encrusting polychaetes from the Early Cretaceous Agrio Formation (Neuquén Basin, Argentina) - Luci, Leticia (2013)
Serpulids and other related tube-dwelling polychaetes are often ignored when found as fossil remains. They are, however, a widespread and important group today, and abundant literature has been published on them. Knowledge of fossil serpulids is centered on European specimens, and little has been done on South American fossil calcareous tubes. In this paper, seven serpulid and sabellid morphotypes are described from the Early Cretaceous marine Agrio Formation of Argentina, revealing a diversity of worms recorded as encrusters on bivalves, ammonites and corals. Sabellids are represented by Glomerula cf. serpentina. Serpulids are represented by two subfamilies: "Serpulinae" includes Mucroserpula mucroserpula, Parsimonia antiquata, Placostegus cf. conchophilus, Propomatoceros semicostatus and P. sulcicarinatus; Spirorbinae is represented by heavily worn tiny coiled tubes assigned to Neomicrorbis?. Serpulids and sabellids are one of the main components of the mollusk encrusting fauna recorded in the Agrio Formation, along with small oysters but much more diverse. They are most commonly found as post-mortem encrusters, but some cases of unquestionable living interaction were also found, remarkably serpulid tubes embedded on coral branches. They are often overgrown by bryozoans, and sometimes by oysters, and frequently occur aggregated.